Survey responses on security of health data - Johnston, David (Cranfield University, 2020)
Responses to a survey "how secure is your health data" on medical information. Collected as part of Information Capability Management MSc research in July 2018: An assessment of blockchain technology for electronic healthcare records in the Ministry of Defence for providing cybersecurity resilience. Contact: dmpjohnston@hotmail.com.
Keywords: 'DMICP'; 'health'; 'information security'; 'medical'; 'Health Information Systems (incl. Surveillance)'